Contribution of Cardiovascular Risk Factors to the Development of Coronary Heart Disease in Kazakhstan - Maidyrov, Yerdan; Zhalmukhamedov, Emil; Perez Hernández, Salma; Díaz Valencia, Luis (Journal of Health Sciences and Medical Development, 2024)
Coronary heart disease (CHD) has well-known risk factors. The prevalence and impact of these mainly depend on people's lifestyles, geography, as well as racial and ethnic predispositions, among other factors. The objective of this study is to compare the prevalence of cardiovascular risk factors among different European and Asian ethnic groups of patients in the Republic of Kazakhstan. The data from 1628 patients diagnosed with coronary angiography for coronary heart disease (CHD) were investigated. SPSS software was used for statistical processing, employing the Kruskal-Wallis test and Chi-square test. The number of patients diagnosed with acute coronary syndrome was 743, and the number of planned patients with stable angina was 885. Approximately 60% of the patients were conditionally categorized as Asians and 40% as Europeans. The gender composition of both groups was dominated by men. There is a general trend towards planned hospitalization in the Asian group (62% vs. 56%, p=0.009). For the specificity of Asian groups, the most significant risk factors were male gender, diabetes mellitus, and overweight. In the European group, the contribution of factors such as arterial hypertension and dyslipidemia (high LDL levels) were found to be more significant. The impact of smoking habits and family history were similar in both groups. In the European group, there was a greater tendency to hemodynamically significant coronary artery atherosclerosis compared to the Asian group (68 vs. 59%, p<0.001), which is hypothesized to be due to overdiagnosis, or the predominance of non-obstructive coronary heart disease in Asian population. Cardiovascular risk factors such as arterial hypertension and dyslipidemia were more prominent in the development of CHD among Europeans, while in Asians diabetes mellitus and being overweight contributed more significantly. Accordingly, it is the above modifiable risk factors that should be given more attention in the prevention and treatment of populations at risk of CHD in Kazakhstan.